1999
DOI: 10.1002/(sici)1096-9063(199910)55:10<971::aid-ps49>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclophosphorothionate antagonists exhibiting selectivity for housefly GABA receptors

Abstract: 2,6,7‐Trioxa‐1‐phosphabicyclo[2.2.2]octane 1‐sulfides (bicyclophosphorothionates) with various C1–4 alkyl groups at the 3‐ and 4‐positions were synthesized and tested for their ability to compete with [3H]4′‐ethynyl‐4‐n‐propylbicycloorthobenzoate (EBOB), a non‐competitive antagonist of γ‐aminobutyric acid (GABA) receptors, for specific binding to rat‐brain and housefly‐head membranes, and for their insecticidal activity against houseflies. Among the 3,4‐substituted analogues, 20 compounds were selectively acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Addition of alkyl side chains to the trioxabicyclooctane moiety in the 3-position ( Fig. 1) resulted in good synergized insecticidal activity, and the compounds had selectivity ratios over 50 for [ 3 H]EBOB binding (rat IC 50 /housefly IC 50 ), in- Archives of Insect Biochemistry and Physiology dicating differential receptor recognition (Ju and Ozoe, 1999). PTX was the first described chloride channel blocker, and other PTX-like natural products are structurally-related terpenoids, including the tutins and picrodendrins (Fig.…”
Section: Gaba Receptor As An Insecticide Targetmentioning
confidence: 99%
“…Addition of alkyl side chains to the trioxabicyclooctane moiety in the 3-position ( Fig. 1) resulted in good synergized insecticidal activity, and the compounds had selectivity ratios over 50 for [ 3 H]EBOB binding (rat IC 50 /housefly IC 50 ), in- Archives of Insect Biochemistry and Physiology dicating differential receptor recognition (Ju and Ozoe, 1999). PTX was the first described chloride channel blocker, and other PTX-like natural products are structurally-related terpenoids, including the tutins and picrodendrins (Fig.…”
Section: Gaba Receptor As An Insecticide Targetmentioning
confidence: 99%
“…The homogenate was filtered through four layers of cheesecloth and centrifuged at 1500g for 10 min, and the supernatant was filtered again and centrifuged at 23 000g for 25 min. The pellet was resuspended in the sucrose-Tris-hydrochloric acid buffer, maintained at 5 °C for 25 min (26), and centrifuged at 23 000g for 25 min. Finally, the pellet was suspended in 10 mM sodium phosphate buffer (pH 7.5) containing 300 mM sodium chloride and used for binding assay.…”
Section: Ethiprole Amide (E-amide) [5-amino-3-carbamyl-1-(26-dichloro...mentioning
confidence: 99%
“…Aiming to develop insecticides with novel structures, we previously synthesized a series of 3,4-disubstituted 2,6,7-trioxa-1-phosphabicyclo[2.2.2]octane 1-sulfides (bicyclophosphorothionates) and investigated their abilities to compete with the noncompetitive GABAR antagonist [ 3 H]EBOB (4 0 -ethynyl-4-n-propylbicycloorthobenzoate) for the binding site in rat brain-and housefly head-membranes, and the structure-activity relationships of some analogs were studied using conventional comparative molecular field analysis (CoMFA) method. 21,22 As a result, we found that bicyclophosphorothionates bearing different substituents at the 3-and 4-positions exhibit various degrees of selectivity between housefly and rat GABARs. Although molecular cloning studies have provided insights into the molecular structures of GABARs, it remains elusive how GABAR-targeting insecticides selectively inhibit the functions of insect GABARs.…”
Section: Introductionmentioning
confidence: 84%